Analisis Peran Kebun Kelapa Sawit Terhadap Kemampuan Penyerapan Karbon di Kabupaten Rokan Hilir - Sumanti, Wiwik; Kadir, Hainim; Iyan, Rita Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Order to determine the development of oil palm expansion in Rokan Hilir and to determine the influence of the expansion of oil palm plantations on the ability of carbon sequestration in Rokan Hilir. The method of analysis used in this study is descriptive qualitative method using the geometric mean. From the results of research on secondary data obtained, indicating the growth of oil palm land area affect forest area, based on the results of the calculation, oil palm plantations grew by 7.17%. Where in 2008 the garden area of 205,537 acres of oil palm, and then increased in 2013 to 271,169.02 acres, while the forest area shrank by 17.6%, whereas in the year 2009 forest area amounted to 683.070 acres, then in 2013 only amounted to 314,229 acres. It also effects the ability of carbon sequestration in forest areas, the ability of forest to absorb carbon decreases as the extent of diminishing returns and has been replaced by oil palm plantations, while the absorption ability of oil palm plantations are not forest's ability to absorb carbon. The ability of forests to absorb carbon in the year 2008 amounted to 52,185,760.42 mg / acres, while in 2013 only amounted to 24,006,733.29 mg / acres, so that carbon stocks were lost due to the development of oil palm expansion of 25744582.5 mg / acres.Keywords: forestry, oil palm plantation, carbon sequestration